Strategi Pelayanan Misi Kontekstual Terhadap Generasi Z Yang Percaya Dengan Memanfaatkan Teknologi Informasi Dan Komunikasi - Oka Astawa; Ayu Rotama Silitonga; Brian Marpay (Predica Verbum: Jurnal Teologi dan Misi, 2023)
Generation Z's tendency to leave the church could occur when the church does not answer the needs and accommodate the generation’s perpectuve . Therefore, mission services to generation Z need to be carried out contextually, requiring services that suit their needs. Contextual mission services must develop the right "strategy" to reach generation Z. The method used is literature study observing books and scientific journals to support research writing. The main topic discussed is contextual mission strategy, where it is necessary to understand culture, Generation Z problems and services for Generation Z in utilizing ICT. Thus, three things were found in this research, firstly, sharing spiritual content via social media, because generation Z can spend quite a long time playing social media. Secondly, carry out spiritual activities online that attract attention creatively and innovatively. Finally, involve generation Z in service, so interest and appreciation might occur in the activities.